THE IMPACT OF POTENTIAL MARKET TOWARDS SHIPPING CARGO VOLUME SURVEY TO EASTERN INDONESIA - Honny Fiva Akira Sembiring; Diana Eka Risky; Sugiyanto Sugiyanto (Institut Transportasi dan Logistik Trisakti, 2018)
The aim of this study is to determine and analyze the impact of potential market towards shipping cargo volume. The lack of modes of transport cause high cost of shipping goods to the eastern Indonesian region. It forces people in Eastern Indonesian region become consumptive. The potential market in Eastern Indonesian region is very large and still very possible to be explored deeper that could be an opportunity for PT AP Logistik Surabaya to attract the customers. This research used both methods of data analysis using simple linear regression analysis, correlation analysis, determinant coefficient analysis and hypothesis testing. The sample was 80 respondents taken from PT AP Logistik Surabaya customer who ship their cargo to Eastern Indonesian region. From the analysis and discussion shows the impact of potential market towards shipping cargo volume which is indicated by a simple linear regression equation is Y = 32,251 + 0.456X, if the Potential Market (X) value is zero (0) or constant, the value of Shipping Cargo Volume (Y) will equal by 32,251. Based on the analysis of the correlation coefficient r = 0,483, meaning that there is influence between (X) and (Y) positive direction and moderate correlation. Determinant coefficient test shows 20.3%, while the remaining is 76.7% which is explained by other variables or factors that is not included in this model. The test result shows that the hypothesis is tscore >ttable (4.8712 > 1.665). Then, H0 is rejected and H1 is accepted. This means that there is significant relationship between potential market towards shipping cargo volume.